Investigating the relationship between watching satellite channels and intimacy and marital satisfaction of couples in Isfahan, Iran, in 2014 - Zohre Babaie; Mahrokh Keshvari; Ahmadreza Zamani (Wolters Kluwer Medknow Publications, 2016)
Background: In the age of communication and media that families are rapidly driven towards using satellite channels and other media, considering family health in this regard is essential. A determinant of health is marital satisfaction. The aim of this study was to investigate the relationship between watching satellite channels and intimacy and marital satisfaction in Isfahan, Iran. Materials and Methods: This cross-sectional and correlational study was conducted on one group of 480 couples (n = 960) participating from 8 health-treatment centers in Isfahan. Multi-stage cluster sampling was used in this study. Inclusion criteria included at least 2 years of marriage. After completion of Bagarozzi's Marital Intimacy Questionnaire and ENRICH Marital Inventory, the couples were divided into two groups based on watching satellite networks. Data were analyzed using SPSS 18. Results: There was a significant relationship between intimacy and marital satisfaction in both viewers and non-viewers of satellite channels (P < 0.050). Average duration of couple's interaction in the satellite viewing group was 22.4 minutes and in non-viewers group was 47.95 min. In addition, the duration of interaction had a significant relationship with marital satisfaction and intimacy (P < 0.050). Conclusions: This study showed that watching satellite channels reduced the intimacy and marital satisfaction of the couples, and duration of interaction among the couples.